Precursors and Moderators of Newcomer Information Seeking and Socialization Tactics: The Influence of Corporate Cultural Intelligence and Corporate Culture (Journal of Organizational Psychology, 2020)
Much of the prior research on newcomer socialization has focused on the tactics used by new employees during their socialization process. However, our knowledge regarding the factors that make newcomers apply particular socialization tactics is limited. In this paper, I propose a theoretical framework that will give us a better understanding of the precursors of newcomer socialization tactics. It is proposed that we can adapt dimensions of cultural intelligence that have traditionally focused on national culture to the study of intelligence relating to the cultures of organizations to predict newcomer information seeking and socialization tactics.
Keywords: Organizational Psychology; newcomer socialization; corporate cultural intelligence; corporate culture